Design and Build The Game "Mickey Adventure Saves His Friend From Monsters" Using The Finite State Machine Method - Arifudin, Muchamat David; Taurusta, Cindy; Suprianto, Suprianto (International Journal on Human-Computing Studies, 2025)
A few years ago, during the pandemic, people tended to experience high levels of stress because they considered the coronavirus to be a dangerous virus, resulting in psychological impacts in the form of fear, anxiety, and stress. To reduce stress due to the pandemic, people work around it by playing games. So with this, the author wants to make a game with the Adventure genre is a good solution in relieving stress during the pandemic, besides that adventure games are games that are easy to understand by all people, from children to adults. Besides relieving stress, Adventure games can train patience and decision-making.